2021
DOI: 10.1101/2021.02.17.431625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rigorous framework for detecting SARS-CoV-2 spike protein mutational ensemble from genomic and structural features

Abstract: The recent release of SARS-CoV-2 genomic data from several countries has provided clues into the potential antigenic drift of the coronavirus population. In particular, the genomic instability observed in the spike protein necessitates immediate action and further exploration in the context of viral-host interactions. Here we dynamically track 3,11,795 genome sequences of spike protein, which comprises 2,584 protein mutations. We reveal mutational genomic ensemble at different timing and geographies, that evol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…2020). Detailed modelling methodology is mentioned in our previous work (Fatihi et al, 2021). The structural mutant model of B.1.617.2 variant was generated using the structural model of ACE2-bound 1 RBD-up spike conformation as a reference.…”
Section: Protein Annotation and Modellingmentioning
confidence: 99%
“…2020). Detailed modelling methodology is mentioned in our previous work (Fatihi et al, 2021). The structural mutant model of B.1.617.2 variant was generated using the structural model of ACE2-bound 1 RBD-up spike conformation as a reference.…”
Section: Protein Annotation and Modellingmentioning
confidence: 99%
“…The crystal structure of different human neutralizing monoclonal antibodies CR3022 6W41 20 , B38 7BZ5 21 , CB6 7C01 22 , P2B-2F6 7BWJ 23 ,and REGN 6XDG 24 were retrieved from PDB RCSB database. In addition, the crystal structure of the hACE2 receptor (PDB ID: 7A97) and S protein (7AD1) was also retrieved 25 .…”
Section: Data Setsmentioning
confidence: 99%
“…67 The multiscale structural modeling and atomistic molecular dynamics (MD) simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile provided the blueprint for biophysical modeling of S proteins. [68][69][70][71][72][73][74] Using deep data analysis and protein structure network modeling of MD simulations, another computational study identified residues that exhibit long-distance coupling with the RBD opening, including sites harboring functional mutations D614G and A570D which points to the important role of D614G variant in modulating allosteric communications in the S protein. 75 The free energy landscapes of the S protein derived from MD simulations together with nudged elastic pathway optimization mapping of the RBD opening revealed a specific transient allosteric pocket at the hinge region that is located near D614 position influences RBD dynamics.…”
Section: Introductionmentioning
confidence: 99%